Hubungan Kecerdasan Emosi, Tingkat Pendidikan Orang Tua dengan Indeks Prestasi Mahasiswa Fakultas Kedokteran Universitas Sebelas Maret Surakarta - Sarah, Ratu Siti Khadijah; Susilohati, Mardiatmi; Iryawan, Andri (Nexus Kedokteran Klinik, 2014)
Background: One important issue in education is academic achievement. Academic achievement can lead to satisfaction and continuity for further education while academic failure can result in delay in learning or even drop out. Some factors that can affect academic result are emotional intelligence as internal factor and parentâs education level (family factor) as external factor. This study aims to prove the existence of relations among emotional intelligence, parentsâ education level and academic achievement index of senior students of Faculty of Medicine, Sebelas Maret University Surakarta. Methods: This study was an observational analytic research with cross sectional approach, held in July â August 2014 in Faculty of Medicine, Universitas Sebelas Maret Surakarta. The sampling method used was total sampling and selection was done by checking the inclusion and exclusion criteria of the study sample. The numbers of subjects in this study were 214 students. Hereafter, the data obtained were analyzed statistically by multiple linear regression test and F test. Results: The results of the F test analysis with the number of significance Î± = 0.05 obtained value of p < 0.05 with a regression line equation Y = 2,660 + 0,004 X1 + 0,010 X2. Conclusions: There is a significant relationship simultaneously between emotional intelligence, level of parentsâ education and index of student achievement. If there is no emotional intelligence and parentsâ education level, the achievement index is equal to 2.660. Index of student achievement changed by 0.004 for each unit change in the variables of emotional intelligence and changed by 0.010 for every unit change in the level of parents education variable. Keywords: Emotional Intelligence, Parentsâ Education Level, Academic Achievement IndexÂ